An epigenetic signature of developmental potential in neural stem cells and early neurons. (4th October 2013) - Burney, Matthew J.; Johnston, Caroline; Wong, Kee‐Yew; Teng, Siaw‐Wei; Beglopoulos, Vassilios; Stanton, Lawrence W; Williams, Brenda P; Bithell, Angela; Buckley, Noel J.
ABSTRACT A cardinal property of neural stem cells (NSCs) is their ability to adopt multiple fates upon differentiation. The epigenome is widely seen as a read‐out of cellular potential and a manifestation of this can be seen in embryonic stem cells (ESCs), where promoters of many lineage‐specific regulators are marked by a bivalent epigenetic signature comprising trimethylation of both lysine 4 and lysine 27 of histone H3 (H3K4me3 and H3K27me3, respectively). Bivalency has subsequently emerged as a powerful epigenetic indicator of stem cell potential. Here, we have interrogated the epigenome during differentiation of ESC‐derived NSCs to immature GABAergic interneurons. We show that developmental transitions are accompanied by loss of bivalency at many promoters in line with their increasing developmental restriction from pluripotent ESC through multipotent NSC to committed GABAergic interneuron. At the NSC stage, the promoters of genes encoding many transcriptional regulators required for differentiation of multiple neuronal subtypes and neural crest appear to be bivalent, consistent with the broad developmental potential of NSCs. Upon differentiation to GABAergic neurons, all non‐GABAergic promoters resolve to H3K27me3 monovalency, whereas GABAergic promoters resolve to H3K4me3 monovalency or retain bivalency. Importantly, many of these epigenetic changes occur before any corresponding changes in gene expression. Intriguingly, another group of gene promoters gain bivalency as NSCs differentiate toward neurons, the majority of which are associated with functions connected with maturation and establishment and maintenance of connectivity. These data show that bivalency provides a dynamic epigenetic signature of developmental potential in both NSCs and in early neurons. Stem Cells2013;31:1868‐1880